2005
DOI: 10.1093/aje/kwi142
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Tornado-related Death and Injury in Oklahoma, May 3, 1999

Abstract: On May 3, 1999, powerful tornadoes, including a category F5 tornado, swept through Oklahoma. The authors examined all tornado-related deaths, hospital admissions, and emergency department visits to identify important risk factors. Data on deaths and injuries directly related to the tornadoes and information obtained from a survey of residents in the damage path of the F5 tornado were used in a case-control analysis. The direct force of the tornadoes caused 40 deaths, 133 hospital admissions, and 265 emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 10 publications
1
52
1
1
Order By: Relevance
“…Tornado fatalities in the United States have been studied over time, by month, by time of day and the day of week, by state/region, by F scale or EF scale rating, by lead time, by place or location of death, by age and sex of the deceased, and so forth (e.g., Daley et al 2005;Ashley 2007;Wurman et al 2007;Simmons and Sutter 2008;Sutter and Simmons 2010;Sutter 2011, 2012;Simmons et al 2012). Simmons and Sutter (2011) have identified four major vulnerabilities for tornado casualties: tornadoes that occur overnight, tornados that occur during the fall/winter months, residence in a mobile home, and location in the United States (specifically, the southeastern part of the United States; see also Schmidlin et al 2009;Chaney and Weaver 2010).…”
Section: Tornado Fatalities: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Tornado fatalities in the United States have been studied over time, by month, by time of day and the day of week, by state/region, by F scale or EF scale rating, by lead time, by place or location of death, by age and sex of the deceased, and so forth (e.g., Daley et al 2005;Ashley 2007;Wurman et al 2007;Simmons and Sutter 2008;Sutter and Simmons 2010;Sutter 2011, 2012;Simmons et al 2012). Simmons and Sutter (2011) have identified four major vulnerabilities for tornado casualties: tornadoes that occur overnight, tornados that occur during the fall/winter months, residence in a mobile home, and location in the United States (specifically, the southeastern part of the United States; see also Schmidlin et al 2009;Chaney and Weaver 2010).…”
Section: Tornado Fatalities: An Overviewmentioning
confidence: 99%
“…If the path passes over highly populated areas, deaths are likely to be higher than if it passes over less populated areas. Tornado deaths also depend on the nature of tornado warnings and compliance with such warnings (Daley et al 2005 (Simmons and Sutter 2011). 3 The number of homes and businesses damaged or destroyed differs not only over time, but also from one source to another.…”
Section: Tornado Fatalities: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…But, Speheger et al (2002) found that only 13% of the total path area affected in the OKC tornado was associated with F4 or F5 damage levels, which is typical of the few F5 tornadoes whose paths have been surveyed reasonably thoroughly. Thus, the other estimates that include either destroyed homes or damaged or destroyed homes [i.e., the Oklahoma Department of Emergency Management, which counted destroyed housing, regardless of the F-scale rating, and Daley et al (2005), based on a survey of residents in damaged or destroyed housing in the path] more accurately reflect the distribution of damage in F5 tornadoes. These fatality rates range from 0.1% to 1%, which are one to two orders of magnitude less than those of W2007.…”
Section: Doi: 101175/bams-89-i-87mentioning
confidence: 99%